ChemInform Abstract: Sunlight‐Driven Hydrogen Peroxide Production from Water and Molecular Oxygen by Metal‐Free Photocatalysts. Issue 11 (March 2015) - Shiraishi, Yasuhiro; Kanazawa, Shunsuke; Kofuji, Yusuke; Sakamoto, Hirokatsu; Ichikawa, Satoshi; Tanaka, Shunsuke; Hirai, Takayuki
Abstract Pyromellitic diimide is incorporated into graphitic carbon nitride, g‐C3N4 by calcination of a mixture of melem and pyromellitic dianhydride at 598 K for 4 h.